Relationship Between Non-Invasive Blood Pressure (NIBP), on First Day of Life with Birth Weight - Chawla, Garima; Maini, Baljeet; Bhardwaj, Anand Kumar (Journal of Nepal Paediatric Society, 2016)
Introduction: India faces lot of neonatal morbidity. Non-invasive blood pressure (NIBP) monitoring is being used for monitoring sick new borns as a safe and cost effective method of blood pressure monitoring. But there is no available information on normal values of NIBP for neonates in India. With more stress of government (and advancement) in new born care, establishing normative data of NIBP in Indian newborns should be high priority. Material and Methods: This was an observational cohort study done in a level III neonatal intensive care unit. 164 clinically stable babies on day 1 of life were included. Blood pressure was measured by the Oscillometric method. Results: Progressive increase of blood pressure was seen with increasing birth weight. 10th, 50th, 75th, 95th Centile curves were drawn from available data. For very low birth weight babies (< 1500grams), the values of systolic, diastolic and mean BP (±2standard deviations (S.D.)) were found to be 53.7 ± 1.7, 29.1 ± 1.7 and 41 ± 1.1 mm Hg respectively. For low birth weight babies, i.e. with birth weight 1500-2499 grams, the values for systolic, diastolic and mean BP(±2 S.D.) were 62.2 ± 2.5, 34.8 ± 2.4 and 46.6 ± 2.4 mm Hg respectively. For normal weight babies (more than 2499 grams), the systolic, diastolic and mean BP (±2 S.D.) were 72.8 ± 4.2, 43 ± 4 and 55.3± 4 mm Hg respectively. The rise in systolic blood pressure with rising birth weight was highly significant (p <0.001). Similar were the results for diastolic and mean BPs, (p<0.001 for both), Conclusion: Blood pressure on day 1 of life appears to be directly related to birth weight. The effect is seen in all (i.e. systolic, diastolic and mean) blood pressure values. J Nepal Paediatr Soc 2015;35(2):141-146